2013
DOI: 10.1007/s12199-013-0357-3
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of progress in the Hokkaido birth cohort study on environment and children’s health: cohort profile—updated 2013

Abstract: The Hokkaido Study on Environment and Children's Health is an ongoing cohort study that began in 2002. The study consists of two prospective birth cohorts, the Sapporo cohort (n = 514) and the Hokkaido large-scale cohort (n = 20,940). The primary goals of this study are to first examine the potential negative effects of perinatal environmental chemical exposures on birth outcomes, including congenital malformations and growth retardation; second, to evaluate the development of allergies, infectious diseases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 80 publications
3
84
0
Order By: Relevance
“…Five previous birth cohort studies have been conducted examining the adverse effects of prenatal PFAS exposure on clinical infectious or allergic disease (Fei et al 2010;Granum et al 2013;Kishi et al 2013;Okada et al 2012;Wang et al 2011). To our knowledge no previous studies have obtained information about fever as such but only about infectious diseases, as assessed by parental questionnaire or hospital diagnosis, and their findings appear to be somewhat inconsistent (Fei et al 2010;Granum et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Five previous birth cohort studies have been conducted examining the adverse effects of prenatal PFAS exposure on clinical infectious or allergic disease (Fei et al 2010;Granum et al 2013;Kishi et al 2013;Okada et al 2012;Wang et al 2011). To our knowledge no previous studies have obtained information about fever as such but only about infectious diseases, as assessed by parental questionnaire or hospital diagnosis, and their findings appear to be somewhat inconsistent (Fei et al 2010;Granum et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two published studies implied BPA exposure to increase the risk of infectious diseases in the pediatric population. One study had suggested prenatal BPA exposure to increase the risk of respiratory tract infection in children; however, the association only became significant after adjusting for confounding factors (32,33). Furthermore, whether the effect of BPA on increased airway infection had resulted from direct immunosuppression or an indirect influence inflicted by hyperactive airway remains debatable, since they had concurrent results showing a strong association between BPA exposure and wheeze/asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The study participants were Japanese mother-child pairs drawn from the birth cohort of The Hokkaido Study on Environmental and Children's Health begun in February 2003 [36][37]. The study protocol has been described [36][37].…”
Section: Selection Of Participantsmentioning
confidence: 99%
“…The study protocol has been described [36][37]. In brief, this is a prospective ongoing birth cohort study.…”
Section: Selection Of Participantsmentioning
confidence: 99%